Uma nova visão para a Galeria Wilson Vaz: o retrofit como ferramenta para requalificação de um ícone comercial de Palmas – TO - Andrade, Isabela Cerqueira (Universidade Federal do Tocantins, 2020)
From the earliest civilizations, commerce and city have a strong link and dependence. One commercial typology that stood out was the commercial galleries, which became an important place for trade in goods. Even after the shopping malls popularization, they still exist, they are still being built, although in some cases, due to several factors, they are in decay, such as the Wilson Vaz Gallery in Palmas-TO. For the reason that it’s a symbolic building and have a great commercial importance for the city, a history and evolution study was made, to understand its apogee and decline. Other similar case studies were also search for to better understand the situation. Given what was observed, it was proposed a requalification of Wilson Vaz Gallery, applying the concepts of Retrofit, seeking to rescue the vitality of the building through architecture.